Impact of Fermented Milk Soaking on Microhybrid Composite Resin Surface Roughness - Irsan Ibrahim; Tuti Alawiyah; Herlin Amelia; Drajat Handika Pakci (Odonto : Dental Journal, 2026)
Background: One type of restorative substance is composite resin, which also comes in microhybrid form. Surface roughness is one of the clinical characteristics that may serve as a predictor of the longevity of restorative materials. The habit of drinking low-pH beverages is one of the things that influences surface roughness. One of the most consumed beverages in society is a fermented milk beverage. Fermented milk is usually safe for consumption by those with sensitivity to dairy products since the bacteria in it can break down lactose into lactic acid. Lactic acid, which has a pH of 4.2–4.8, is found in fermented milk. The purpose of this research is to ascertain how soaking fermented milk affects the microhybrid composite resin's roughness. Methods: This study uses a pre-test post-test design methodology and is conducted in a laboratory setting. There are 27 samples of microhybrid composite resins that are conducted with fermented milk. Prior to and following immersion, the surface roughness of the microhybrid composite resin was measured using a surface roughness tester as part of this study. Results: On the first through the seventh day of immersion, there was a noticeable rise in the surface roughness of the Microhybrid composite resin submerged in fermented milk. Conclusion: After being immersed in a solution of fermented milk for one, four, and seven days, the nanohybrid composite resin is affected by its roughness.